Humor in Contemporary Native American Art - Ayari, Hend (AMERICANA E-journal of American Studies in Hungary, 2023)
Humor is a central feature of Native American culture as it manifests itself in various facets of tribal life. In the past, humor ensured the survival of tribes as it facilitated communication and built a stronger sense of kinship. The “Stoic Indians” stereotype gradually took over hence the supposedly Stoic Indians have been denied the right to access to today’s American “laughscape” (Rebecca Krefting). Traditionally, humor has been closely aligned with literature (satirical writings) or performance (comedic plays) but rarely with visual arts. Thus, the contribution of contemporary Native American visual artists is twofold: (1) to introduce and highlight the humor in visual arts and (2) to manipulate this strategy as a tool for cultural transmission and identity reclamation. In so doing, Native American artists, like any other ethnic and racial group, recognize the power of humor as a tool that brings people, regardless of their ethnic background, “to a militant edge” to use Vine Deloria’s term. Humor expressed through these artists’ creations serves as a repository for tackling issues related to the Native American experience and the whole country. In terms of methodology, an analysis of a selection of contemporary artwork by Native American artists such as Jim Denomie, Wendy Red Star and Tom Farris that combine features of satire, parody, and puns yields the conclusion that humor in visual art is commensurate with examples from the field of literature and performance. The other outcome of this examination is a humorous artistic attempt at breaking down the negative cultural stereotypes and participating in the re-invention of a resilient American Indian identity. Both aspects of this paper are rooted in ethnic humor studies.